Phytochemical Study On The Shoots Of Dendrocalamus Asper, And Synthesis Of Pyrazoline Derivatives And Their Biological Activities - Wong, Kok Tong (2021)
This thesis consists of two parts. The first part is phytochemical study on the shoots of Dendrocalamus asper. The second part, pyrazoline had been found in this plant, however, not many biological studies have been done on its derivatives. Pyrazoline derivatives also can be synthesised through cyclocondensation reaction.